Gender Stereotyping in Schools: A Study in Rural Assam - Das, ADITI (International Journal of Psychosocial Rehabilitation, 2024)
Developing countries face number of problems such as poverty, unemployment, malnutrition, poor educational infrastructure, of which one of the most fundamental problems is the gender disparity in schooling. School enrolments of girls are lower than the boys indicating that girls are disadvantaged in access to education. Apart from various factors that affect gender disparity in schooling, an important fundamental constraint that restricts attainment towards gender equality is gender stereotyping in school especially in class room activity. This paper tries to identify whether gender stereotype exist in the classroom activity in the schools under study. 18 government schools have been selected from six blocks from three districts of Assam and a sample of 90 in service teacher has been collected. A semi structured interview was also conducted to understand the attitude of the teacher towards gender stereotyping in class room activities.